2009
DOI: 10.1037/a0018008
|View full text |Cite
|
Sign up to set email alerts
|

Improving memory after interruption: Exploiting soft constraints and manipulating information access cost.

Abstract: Forgetting what one was doing prior to interruption is an everyday problem. The recent soft constraints hypothesis (Gray, Sims, Fu, & Schoelles, 2006) emphasizes the strategic adaptation of information processing strategy to the task environment. It predicts that increasing information access cost (IAC: the time, and physical and mental effort involved in accessing information) encourages a more memoryintensive strategy. Like interruptions, access costs are also intrinsic to most work environments, such as whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
64
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(77 citation statements)
references
References 85 publications
11
64
2
Order By: Relevance
“…If stacked display users experience relatively higher information access cost, they should try to overcome the cost by spending extra encoding time to facilitate later retrievals from memory (Morgan, Patrick, Waldron, King, & Patrick, 2009). As predicted, participants in the stacked display condition fixated significantly longer on information pieces on each page during their first visit to each page (called first-pass fixations) than those who solved the same problem using the distributed display.…”
Section: A Three-factor Framework For Understanding Visual Informatiomentioning
confidence: 74%
“…If stacked display users experience relatively higher information access cost, they should try to overcome the cost by spending extra encoding time to facilitate later retrievals from memory (Morgan, Patrick, Waldron, King, & Patrick, 2009). As predicted, participants in the stacked display condition fixated significantly longer on information pieces on each page during their first visit to each page (called first-pass fixations) than those who solved the same problem using the distributed display.…”
Section: A Three-factor Framework For Understanding Visual Informatiomentioning
confidence: 74%
“…Studies of high access cost (e.g., Morgan et al, 2009, Experiment 1) reported large effect sizes (f = .76 -.97) on strategy measures. Statistical power for all four experiments was calculated using G*Power 3.1.7 software (Faul, Erdfelder, Lang, & Buchner, 2007;Faul, Erdfelder, Buchner, & Lang, 2009).…”
Section: Participantsmentioning
confidence: 99%
“…Inducing a more memory-based strategy by increased access cost can: (a) mitigate the negative effects of interruption by reducing forgetting post-interruption (e.g., Morgan et al, 2009); (b) encourage better use of an interruption lag, which is a short delay before an interrupting task that provides an opportunity to encode suspended goals for retrieval postinterruption ; and (c) also encourage better planning and solution efficiency in problem solving . The focus of the theory of soft constraints (Gray et al, 2006) is on the effect of constraints of the task environment on performance and is consistent with a wide-ranging literature suggesting that many aspects of behavior are controlled by short-term rather than long-term tradeoffs (e.g., Hernstein & Vaughn, 1980;Loewenstein, Read, & Baumeister, 2003).…”
Section: The Theory Of Soft Constraintsmentioning
confidence: 99%
See 2 more Smart Citations